(untitled) (Human Factors in Design, 2013)
This paper is focused on improving an ergonomic ear coupled with goggles, to meet the needs of operators working in areas where noise is excessive, above 100 to 114 dB (A), as Norm NR-15 and also require goggles. The main function is to give comfort to the workers of operational areas where the use of protective eyewear and ear shell type is essential to perform their daily functions. The coupling to the ear of the glasses is composed of rod adjustable with a quick release pin. Research ergonomic case with the development of a virtual representation and propose a different stakeholder groups to evaluate the new model in the degree of acceptability.